CONGENITAL SYPHILIS: PRENATAL CARE AND TREATMENT OF PREGNANT WOMEN AND THEIR PARTNERS - Jéssica Strube Holztrattner; Graciele Fernanda da Costa Linch; Adriana Aparecida Paz; Helga Geremias Gouveia; Débora Fernandes Coelho (Universidade Federal do Paraná, 2019)
Objective: to analyze the onset and association of congenital syphilis with prenatal care and treatment of pregnant women and their partners.Method: Retrospective observational study conducted in the 2006-2015 period based that looked at data from Brazil, Rio Grande do Sul and Porto Alegre, based on indicators of the Brazilian Ministry of Health.Results: The rate of congenital syphilis in children under one year of age increased from 2 to 6.5 in Brazil; from 1.5 to 11.5 in Rio Grande do Sul, and from 4.4 to 30.2 in Porto Alegre. Around 74% of women performed prenatal care at the municipal, state and federal levels. Of the total number of pregnant women, 80% were not treated or were improperly treated. The percentage of treatment of their partners did not exceed 20.5%. Conclusion: The present study reported an increase in the onset of congenital syphilis. Moreover, prenatal care did not ensure adequate treatment of pregnant women and their partners.